Congestion and overload control techniques in massive M2M systems: a survey. Issue 2 (27th March 2015) - Ferdouse, Lilatul; Anpalagan, Alagan; Misra, Sudip
Abstract: Smart applications, Internet of things, cloud computing technologies are becoming connected together by autonomous and intelligent devices. Communication among those devices, called machine‐type communication (MTC) can be done through cellular networks. A cellular network typically handles both voice and data traffic. Cellular based machine‐to‐machine (M2M) communication utilises cellular infrastructure to convey their information among MTC devices. Although MTC devices generate small amount of data traffic, massive amount of MTC devices create overload problem which hugely impacts the radio access and core networks of the cellular system. This article discusses M2M systems, its various applications, architectural requirements, functionalities, services and features from congestion and overload control point of view. In particular, a survey of congestion control problem in M2M systems and its various solutions are discussed in this article. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The survey presents a critical review of various solution techniques for massive access request problem in cellular machine‐type‐communication (MTC) systems. A general overview of a typical MTC system, its various applications, architectural requirements, functionalities, services, and features are first discussed. Then, the scenario of overload problem and comparative analysis of different solution methods applicable for radio access and core network of the cellular MTC systems are elaborately described and classified. Lastly, some improvement areas of the existing solutions and possible research directions are presented.